Japan and Indonesia as Middle Powers in Indo-Pacific: Towards AOIP – FOIP Synergy - Rafyoga Jehan Pratama Irsadanar (Kementerian Luar Negeri Republik Indonesia, 2023)
This paper studies how a strategic bilateral relations between middle powers could advance the realization of a larger regional geostrategy. This paper took Indonesia - Japan relations to study how the two countries’ strategic partnership could accelerate the realization of an inclusive, safe and well-connected Indo – Pacific area. Using middle power framework in international relations, this qualitative research paper sees that Indonesia and Japan are “assembler” type of middle powers in Indo-Pacific. This paper argues that two or more middle powers with solid regional leadership and shared geostrategic vision could get more partners to be on board to support the shared geostrategic agenda. This paper found that intensified engagement between Indonesia and Japan, as assembler middle powers, could advance the implementation of ASEAN Outlook on the Indo-Pacific (AOIP) and accelerate the synchronization of ASEAN Outlook on the Indo-Pacific and Free and Open Indo-Pacific (FOIP). Contributing to the study of middle power in international relations, this finding implies that middle powers have a significant role in realizing a geopolitical vision, despite not as influential and powerful as great powers.